Transformation of the modern facilities of hostility conduct - Ivanitskyi, R. S. (Honor and Law, 2019)
Matter of transformation modern facilities of hostility conduct, increasing the influence upon upshot of the hostilities untraditional facilities such as information, unmortal and ecological weapon is considered.